PROFIL MODEL PEMBELAJARAN SENI BACA ALQUR'AN PADA TINGKAT SEKOLAH DASAR DI MAJELIS TA'LIM DAARU TA'ALLUMIL QUR'AN - fatonah fatonah; Bunga Jannahtu Sholeha; Ahmad Luthfi Hidayat (Al Naqdu, 2021)
One of these coaching institutions for the art of reading the Alqur'an is the Majelis Ta'lim Daaru Ta'allumil Qur'an in the Kemanten Cirebon. Researchers choose this institution as objects in research due to seeing the high enthusiasm of students in learning the art of reading the Alqur’an. Which aims to understand how is the learning model for the art of reading the Alqur'an, especially at the elementary school level. Research methods is qualitative methods with descriptive study approaches, data collection techniques are observation for 25 days, interviews, and documentation. The results of the study found that the learning levels were divided into three classes. There are two kinds of art of reading the Alqur'an with seven nagham’s. The learning system applied are blended learning, repetition of maqro verse for 3-4 months at each meeting, differences in the selection of verses, and the beheading of words in each verse. Furthermore, scheduled activities are daily activities, weekly, annual and urgent activities such as special coaching for the Musabaqah Tilawatil Qur’an (MTQ) competition in certain institutions. And the learning method applied are the combination of the sima'i and tausyikh methods.